Improving the Transient Stability of the Mixed AC/DC Networks with FACTS - Ayachi Bilel; Ahcene Boukadoum; Salah Leulmi; Tahar Boukra (IAES Indonesian Section, 2018)
It is probable that future power transmission systems will contain more HVDC-VSC links (High Voltage Direct Current-Voltage Source Converter) leading to a growing complexity in the study of its problem and so do the transient stability problems which are yet to be determined. In this context, this paper presents an efficient method to resolve this problem. Its main objective consists of improving transient stability of the AC/DC (Alternating Current/ Direct Current) power system network using FACTS (Flexible Alternating Current Transmission Systems). The overall performance of the FACTS was evaluated in an IEEE 14 bus test system by nonlinear simulations carried out using Matlab environment to check the performance of FACTS (TCSC, Thyristor Controlled Series Capacitor). The obtained results showed the effectiveness and robustness of FACTS in improving the transient stability of the systemt.